Strategy For Developing Traditional Night Market Pt Safaria Adi Puta - Epi Hasnarella; Hendri Dunan (International Journal of Economics, Business and Innovation Research, 2026)
This study examines the development strategies of traditional night markets implemented by PT Safaria Adi Putra, emphasizing the role of leadership and local socio-cultural values in sustaining business performance. A qualitative case study approach was applied, using data collected through observations, in-depth interviews, and documentation. The findings indicate that development strategies include standardization of facilities, structured spatial management, digital promotion, and cultural-based entertainment innovation. Managerial leadership strengthens coordination, trader participation, and stakeholder trust, while socio-cultural values such as mutual cooperation and community bonding enhance market sustainability. The study concludes that the integration of adaptive development strategies, participatory leadership, and socio-cultural values is essential to improving the competitiveness and sustainability of traditional night markets.